2010
DOI: 10.1002/chem.201001143
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Ru‐Catalyzed Semireduction of Alkynes to Z Olefins under Transfer‐Hydrogenation Conditions

Abstract: By using a readily available, air- and moisture-stable dihydrido-Ru complex, a variety of Z olefins are accessible under transfer-hydrogenation conditions with formic acid as the hydrogen source in excellent yields and Z/E selectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 80 publications
0
29
0
2
Order By: Relevance
“…Particular focus has been put on the selective catalytic transfer hydrogenation of alkynes,5 using water5e,f,i or organic hydrogen donors, such as alcohols,5d carboxylic acids,5a,b,g,i and amines 5h. These methods are relatively mild, safe (avoiding the use of a potentially hazardous pressurized H 2 atmosphere), and in some cases environmentally friendly.…”
Section: Methodsmentioning
confidence: 99%
“…Particular focus has been put on the selective catalytic transfer hydrogenation of alkynes,5 using water5e,f,i or organic hydrogen donors, such as alcohols,5d carboxylic acids,5a,b,g,i and amines 5h. These methods are relatively mild, safe (avoiding the use of a potentially hazardous pressurized H 2 atmosphere), and in some cases environmentally friendly.…”
Section: Methodsmentioning
confidence: 99%
“…By comparing the performance, the broad scope, and the environmental friendliness of our Pd 0 ‐AmP‐HSN/DMSO system, it can be concluded that it compares favorably to many of the recently developed catalytic protocols for the partial reduction of alkynes. For example, it has the advantage of affording high yields of alkenes under milder reaction conditions, whereas other catalytic systems require higher catalyst loadings, higher H 2 pressures, and elevated reaction temperatures . Particularly noteworthy in this regard is that our catalytic system is comparable in performance to a number of homogenous Pd protocols .…”
Section: Resultsmentioning
confidence: 98%
“…Transition metal‐catalyzed semihydrogenation of alkynes is one of the most straightforward methods for synthesis of such alkenes. In the past decades, remarkable achievements have been made and lots of efficient reactions such as Pd‐,6 Rh‐,7 Ir‐,8 Ru‐,9 and V‐10 catalyzed systems have been reported for the hydrogenation of alkynes to give alkenes. However, replacement of precious metals,11 safe hydrogen sources12 and over‐hydrogenation13 are still the key issues for this hydrogenation reaction.…”
Section: Methodsmentioning
confidence: 99%